Major carbon losses from degradation of Mauritia flexuosa peat swamp forests in western Amazonia - Hergoualc'h, Kristell; van Lent, J.; Dezzeo, N.; Verchot, L.V.; van Groenigen, J.W.; López Gonzales, M.; Grandez-Rios, J. (Springer, 2023)
Tropical peat swamp forests are major global carbon (C) stores highly vulnerable to human intervention. In Peruvian Amazonia, palm swamps, the prevalent peat ecosystem, have been severely degraded through recurrent cutting of Mauritia flexuosa palms for fruit harvesting. While this can transform these C sinks into significant sources, the magnitude of C fluxes in natural and disturbed conditions remains unknown. Here, we estimated emissions from degradation along a gradient comprising undegraded (Intact), moderately degraded (mDeg) and heavily degraded (hDeg) palm swamps. C stock changes above- and below-ground were calculated from biomass inventories and peat C budgets resulting from the balance of C outputs (heterotrophic soil respiration (Rh), dissolved C exports), C inputs (litterfall, root mortality) and soil CH4 emissions. Fluxes spatiotemporal dynamics were monitored (bi)monthly over 1–3 years. The peat budgets (Mg C ha−1 year−1) revealed that medium degradation reduced by 88% the soil sink capacity (from − 1.6 ± 1.3 to − 0.2 ± 0.8 at the Intact and mDeg sites) while high degradation turned the soil into a high source (6.2 ± 0.7 at the hDeg site). Differences stemmed from degradation-induced increased Rh (5.9 ± 0.3, 6.2 ± 0.3, and 9.0 ± 0.3 Mg C ha−1 year−1 at the Intact, mDeg, and hDeg sites) and decreased C inputs (8.3 ± 1.3, 7.1 ± 0.8, and 3.6 ± 0.7 Mg C ha−1 year−1 at the same sites). The large total loss rates (6.4 ± 3.8, 15.7 ± 3.8 Mg C ha−1 year−1 under medium and high degradation), originating predominantly from biomass changes call for sustainable management of these peatlands.